2012
DOI: 10.2174/1874325001206010582
|View full text |Cite
|
Sign up to set email alerts
|

Occult Acetabular Fracture in Elderly Patients

Abstract: Acetabular fractures in the elderly are increasingly common; however, an antecedent of trauma may not be known, and the diagnosis easily missed. Early identification and prompt management are needed in order to minimise morbidity rates, but little has been published on occult acetabular fracture.In this paper we present three cases of occult acetabular fracture in patients older than 75 years. All three are females and had previously been operated on the ipsilateral hip with an implant (two proximal femur frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“… 23 This might be due to the rise of age-adjusted incidence of osteoporosis, 26 or the application of more sensitive diagnostic imaging including computed tomography and magnetic resonance imaging in diagnosing the “occult” acetabular fractures. 27 28 29 Using the French registry, Melhem et al 17 estimated 19% increase of acetabular fractures in 2030 compared to 2016. This is especially in line with the projected increase of the acetabular fractures to 2030 found in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 23 This might be due to the rise of age-adjusted incidence of osteoporosis, 26 or the application of more sensitive diagnostic imaging including computed tomography and magnetic resonance imaging in diagnosing the “occult” acetabular fractures. 27 28 29 Using the French registry, Melhem et al 17 estimated 19% increase of acetabular fractures in 2030 compared to 2016. This is especially in line with the projected increase of the acetabular fractures to 2030 found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…describieron una serie de pacientes >75 años a quienes se les había diagnosticado una fractura oculta del acetábulo secundaria a la osteosíntesis endomedular para tratar una fractura de cadera. 16 No debe dejarse de lado la evaluación por imágenes de la columna, porque la cifosis lumbar degenerativa y otras alteraciones del balance espinopélvico podrían ser factores predisponentes. 17 Sin embargo, en el caso reportado, nuestra paciente no tenía alteraciones en el espinograma.…”
Section: Discussionunclassified
“…In our case, the symptoms of the medial wall acetabular fracture were masked by concomitant ramus/ischium fractures. In previous studies, CT and MRI were reportedly useful for identifying fracture lines that were not visible on radiography [ 18 , 25 , 26 ]. Mandell et al [ 27 ] reported that in the clinical setting of suspected occult fracture, the sensitivity of clinical CT results for detecting pelvic fractures was 88%, the specificity was 98%, and the negative predictive value was 94%.…”
Section: Discussionmentioning
confidence: 99%